ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PADA YAYASAN BALI SARASWATI DI GIANYAR - Made Ayu Desy Geriadi; Bagus Arya Wijaya; Ni Putu Ade Augustyana Barintha Dewi (Jurnal Ilmiah Satyagraha, 2024)
Financial ratio analysis is an effort to find a picture of relationships and compare the number of accounts when describing financial reports. By using financial ratio, internal and external parties to an entity can easily obtain information about the entity's strengths and weaknesses from a financial perspective. The financial performance of the Yayasan Bali Saraswati cannot be said to be good because the profits it generates are still decreasing and increasing every year, so a financial ratio analysis calculation is needed which is one way to assess the financial performance of the Yayasan Bali Saraswati. By calculating existing financial ratio, it will be possible to know the financial performance conditions currently being experienced by the Yayasan Bali Saraswati. The formulation of the problem in this research is how the financial performance of the Yayasan Bali Saraswati in Gianyar for the 2018 - 2022 period is measured by financial ratio. The aim of the research is to determine the financial performance of the Yayasan Bali Saraswati in Gianyar for the 2018 - 2022 period as measured by financial ratio. Data were analyzed using 4 financial ratio, namely liquidity ratio, solvency ratio, activity ratio and profitability ratio. The results of the research show that the financial performance of the Yayasan Bali Saraswati seen from the liquidity ratio, solvency ratio and profitability ratio is good, while seen from the activity ratio in the indicator Working Capital Turn Over and Total Assets Turn Over are in poor condition.